PENERAPAN PEMBELAJARAN METODE TIME TOKEN ARENDS (TTA) UNTUK MENINGKATKAN KEMAMPUAN BERTANYA DAN HASIL BELAJAR MATA PELAJARAN EKONOMI SISWA KELAS X IIS 4 DI SMAN 1 BATU - Oktavia Nardiani; Sapir Sapir; Sugeng Hadi Utomo (Universitas Negeri Malang, 2015)
This study uses a Class Action Research conducted in two cycles. The subjects were students of class X IIS 4 in SMAN 1 Batu with the number of students as many as 28 students consisting of 9 male students and 19 female students. Data collection techniques in this study includes observation, interviews, field notes, student questionnaire responses, the issue of pre-test and post-test, and documentation.From the series of data analysis results and the ability to ask students' learning outcomes by implementing learning methods Time Token Arends (TTA) in the first cycle and the second cycle has increased significantly and the results of this study to get a positive response from teachers and students of class X IIS 4. Thus, recommended for teachers to implement teaching methods Time Token Arends (TTA) to improve the ability to ask and learning outcomes, as well as to avoid students who dominate in learning.